Application of bismuth sulfide based nanomaterials in cancer diagnosis and treatment. (April 2023) - Yang, Zhongwei; Wang, Longwei; Zhang, Jian; Liu, Jing; Yu, Xin
Abstract: Cancer is still the leading disease threatening human life and health at present. With the development of nanotechnology, multifunctional nanomaterials integrated with different diagnostic and therapeutic functions have become the most active field in nano-research. Among them, Bi2 S3 -based nanomaterials have attracted great attention in the biomedical field due to their special photothermal effect and biocompatibility. In this review, we systematically summarize the synthetic strategies and their physical-chemical properties of Bi2 S3 -based nanomaterials. Then we outline the recent research progress in the diagnosis and treatment of cancer, which are highlighted and discussed in detail. In addition, the safety and biodistribution of Bi2 S3 -based nanomaterials are emphasized and discussed. It is believed that the emerging Bi2 S3 -based nanomaterials may realize the practical applications via unremitting efforts of scientific researchers in the near future. Graphical Abstract: ga1 Highlights: This review summarizes the recent significant progress in the diagnosis and treatment of cancer of Bi2 S3 -based nanomaterials. Synthetic strategies for Bi2 S3 -based nanomaterials and their physical-chemical properties are discussed. Perspectives on the future opportunities and challenges of Bi2 S3 -based nanomaterials are provided.